2020
DOI: 10.1371/journal.pone.0239814
|View full text |Cite
|
Sign up to set email alerts
|

Molecular endoscopic imaging for the detection of Barrett’s metaplasia using biodegradable inorganic nanoparticles: An ex-vivo pilot study on human tissue

Abstract: Background and study aims Despite major technical advancements, endoscopic surveillance for detecting premalignant lesions in Barrett's esophagus is challenging because of their flat appearance with only subtle morphological changes. Molecular endoscopic imaging (MEI) using nanoparticles (NPs), coupled with fluorescently labeled antibody permits visualization of disease-specific molecular alterations. The aim of this ex vivo study was to assess the diagnostic applicability of MEI with NPs to detect Barrett's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…NPs may be clinically useful because of their properties, such as a spherical shape and small diameter from 10 to 90 nm, and they can distribute widely in Barrett’s mucosa to penetrate biological barriers of the mucosa. Ahmed et al revealed the diagnostic specificity of FITC-conjugated Muc-2 antibodies for the identification of goblet cells of metaplasia in biopsy specimens from all BE patients [ 75 ]. Despite the lack of evidence of the NPs for neoplastic BE, various candidate peptides have been investigated to achieve high sensitivity and specificity for diagnosing Barrett’s neoplasia [ 65 , 76 , 77 ].…”
Section: Non-endoscopic and Endoscopic Technologiesmentioning
confidence: 99%
“…NPs may be clinically useful because of their properties, such as a spherical shape and small diameter from 10 to 90 nm, and they can distribute widely in Barrett’s mucosa to penetrate biological barriers of the mucosa. Ahmed et al revealed the diagnostic specificity of FITC-conjugated Muc-2 antibodies for the identification of goblet cells of metaplasia in biopsy specimens from all BE patients [ 75 ]. Despite the lack of evidence of the NPs for neoplastic BE, various candidate peptides have been investigated to achieve high sensitivity and specificity for diagnosing Barrett’s neoplasia [ 65 , 76 , 77 ].…”
Section: Non-endoscopic and Endoscopic Technologiesmentioning
confidence: 99%